ANALISIS RANTAI PASOK (SUPPLY CHAIN) JAGUNG PIPIL (studi pada PT. Jatinom Indah Agri Blitar) - Alamulhuda, Atssiqif; Kurniastuti, Tri (grafting, 2024)
This study aims to determine the flow of supply chain management for Shelled corn, to determine the value of marketing efficiency of corn supply chain in PT. Jatinom Indah Agri and to find out the profit ratio on the parties involved in the shelled corn supply chain. The research method used is a quantitative descriptive method. The results of the research from the supply chain analysis are the results of a margin share of Rp. 700/kg for collectors and Rp. 150/kg for PT. Jatinom Indah Agri, then the total amount of margin obtained is Rp. 850/kg. The marketing cost incurred by the collector or supplier is Rp. 550/kg for the cost of expedition vehicles (fuso or containers) for delivery to the warehouse of PT. Jatinom Indah Agri Blitar and Rp. 80/kg for the cost of weighing and loading shelled corn to the top of the expedition vehicle. C osts incurred by PT. Jatinom Indah Agri is a fee or fee of Rp. 50/Kg for workers or people who help find pipil corn and help negotiate prices from collectors to be sent to PT. Jatinom Indah Agri. The profit obtained is Rp. 100/kg, the total profit obtained is Rp. 170 per kg, the total margin of the shelled corn supply chain is Rp. 850 per kg. The efficiency of the supply chain obtained is 11.8%, which is said to be efficient if the percentage is 0-33%. So the results obtained in the pipil corn supply chain are efficiently carried out and the measurement of the R/C ratio in the shelled corn supply chain has a total result of 2.11, which is said to be relatively favorable if the R/C value is more than (<) 1. So the results of measuring the supply chain of shelled corn with the R/C ratio get relatively favorable results.